2010
DOI: 10.1111/j.1460-9592.2009.03241.x
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil in children

Abstract: SummaryRemifentanil has gained the confidence of anesthesiologists and has given a real opportunity to change the way anesthesia is given. It can be considered the ideal opioid despite many obstacles to pediatric use: the condition of 'off-label', the lack of wide randomized clinical trials, and the fear of adverse events because of its high potency. Experiences in the field with this opioid over the years encouraged its use. Use has been associated with N 2 0 and volatile agents for general anesthesia and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 87 publications
(88 reference statements)
0
22
0
1
Order By: Relevance
“…This can be explained by pharmacodynamic drug properties, rapid concentration decrease, and rapid termination of effect after the application (8). It is of great importance to have experience and knowledge of the remifentanil properties because a prompt analgesic treatment of postoperative pain is required, often to be started during the surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by pharmacodynamic drug properties, rapid concentration decrease, and rapid termination of effect after the application (8). It is of great importance to have experience and knowledge of the remifentanil properties because a prompt analgesic treatment of postoperative pain is required, often to be started during the surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that remifentanil decreases postoperative delirium. 16 Dizziness after ketamine use is common as a result of transient diplopia. 3 In contrast, patients who received ketamine with remifentanil in the present study showed reduced rates of dizziness, probably because of the use of remifentanil and smaller doses of ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…13 -15 Remifentanil is an ultra-short-acting opioid, without an active metabolite, that provides effective sedation, rapid onset, rapid recovery, easy titration, reduced nausea and vomiting, and decreased postoperative delirium. 16 Thus, remifentanil can be administered as an adjuvant to ketamine, for brief procedures. Reports in the literature about the combined administration of ketamine and remifentanil are, however, rare.…”
Section: Introductionmentioning
confidence: 99%
“…Remifentanil is well suited for analgo-sedation during short painful procedures, but a less favorable option for postoperative pain control in non-ventilated or sedated children owing to its short duration of action [161], and has gained wide acceptance [162][163][164]. Studies elucidating the PK-pharmacodynamic relationship are particularly needed in children of all age groups because of its popularity [165].…”
Section: Intravenous Remifentanilmentioning
confidence: 99%